(untitled) (Indian Journal of Arid Horticulture, 2018)
Agricultural production systems have so far successfully addressed the national requirements of agricultural products through increasing productivity by the large scale use of non-renewable resources and simplification of production systems achieved by transition from mixed farming to specialized farming. This intensification of agricultural production systems has led to many negative environmental consequences like loss of biodiversity, degradation of soil and water resources, enhancing the greenhouse gas emission, declining profitability, increasing risks and inadequate employment and has thus raised the concerns about the economic, environmental and social costs of this success. Therefore, it is imperative to design and implement new agricultural production systems, to enhance farm productivity & profitability, environmental quality, resource use efficiencies along with improving household nutritional security. These seemingly diametrically opposed objectives could be simultaneously achieved by implementation of integrated farming systems approach (IFS). This paper describes the significances of IFS in terms of enhancing productivity, profitability, employment generation, resource conservation and adaptation and mitigation to anticipated climate change with special reference to arid and semi-arid regions of India. The major constraint in implementation of IFS, and suggestion for enhancing their large scale adoption are discussed.